Inhabiting a Transborder Territory: Non-Formal Educational Proposal Addressed to Rural Youths from the Canton of Upala, Alajuela, Costa Rica - Salas-Acuña, Erick Francisco (2020)
This paper describes a non-formal education proposal developed in the cross-border canton of Upala, Alajuela, Costa Rica. The educational process was carried out during 2017 with the participation of young people belonging to the Network of Young Immigrants and Transborder, who participated in a series of workshops aimed at reflecting on what it means to inhabit a transboundary rural territory. It starts from the fact that young people constitute a population marked by a structural exclusion based on adult-centered notions that, in the particular case of this area, take on even greater dimensions due to the condition of rurality and immigration that has historically characterized these populations. Upala, a trans-border rural canton in the northern region of the country, constitutes a territory whose particular dynamics reflect a complex social reality rarely addressed by the economic, cultural and educational policies of the governments of the day. This project is an effort to serve this vulnerable population in order to reflect on their status as young rural migrants. It is argued in favor of the need to promote the inclusion of these groups through governmental initiatives more in keeping with the conditions of these regions.